Rancang Bangun Aplikasi Media Pembelajaran IPA Berbasis Macromedia Flash untuk Siswa Sekolah Dasar - Hamzah Hamsir (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This study aims to produce science learning media for grade 5 of elementary school based on Macromedia Flash. This research was conducted using the R&D (Research and Development) method and the staged model of this research used the Waterfall model or what is often referred to as the waterfall model. The results of this study is Desktop-Based Science Learning Media Application for grade 5 elementary. This Application is consisting of main menus such as KI and KD menus, objectives menu, material menu, quiz menu, about menu and profile menu. This application has been tested using the Black Box method and tested by multimedia expert lecturers. It can be concluded that all button page views have functioned properly so that this learning media application is feasible to use.